The barriers of e-book project implementation among primary school teachers in Dungun, Terengganu / Nurul Izatee Md Yusoff - Md Yusoff, Nurul Izatee (2012)
The research aims to find the extent of E-book project adoption among primary school teachers in Terengganu. E-book project, as a matter of fact is not mainly the implementation of electronic books, but the major purpose is to utilize the existence of latest technology of one-to-one computer interaction in classrooms. Furthermore, it also aims to find the relationship between the teachers' ICT competencies and their frequency of implementing the E-book project which inclusive of a computer and/or the electronic books, in classrooms. A survey questionnaire was designed and distributed to 23 respondents teaching in Year Four, Five and Six of Sekolah Kebangsaan Pusat, Dungun, in order to answer the research questions formulated, both quantitative and qualitatively. The results of the finding have shown that the teachers7 ICT competencies do not positively influence the frequency of E-book project implementation in classrooms. Thus, it can be concluded that there are barriers in hindering the implementation of E-book project in primary schools and the findings have shown that majority of the respondents agreed that lack of time and workloads burden are the major barriers on why they were unable to implement the E-book project in daily lessons.